Strictly ballroom dancing. Vol. 2 : non-stop cha cha. (A Plum Music Production/Alpha Records Corp, 1997)
[1.] Magic carpet ride. -- [2]. Tic Tic Tac. -- [3]. Oye Como Va. -- [4]. Chiquita Bonita. -- [5]. Carmelita. -- [6]. Oh Carol. -- [7]. Beautiful Sunday. -- [8]. Pepito. -- [9]. Knock three times. -- [10]. Candida. -- [11]. Sweet and gentle. -- [12]. Jamaica farewell. -- [13]. Once on a Sunday morning. -- [14]. I write your name through the fire. -- [15]. South of the border. -- [16]. Devil woman. -- [17]. Santa Monica. -- [18]. Papa loves mama. -- [19]. Dancing in the sun. -- [20]. Evil ways.
Keywords: Ballroom dancing